Can You Make Money from Being Queer? Commodification of Queerness on Social Media as Biographical Experience - Drążczyk, Aleksandra (Qualitative Sociology Review, 2025)
The article presents a case study of an autobiographical narrative interview with Adam—a young influencer who creates books-related content. Special attention is given to Adam’s relationship with his audience and how it influences his self-perception. Of significant importance to the influencer’s biography are Adam’s non-heteronormative sexual orientation and the stigma associated with it. Using the sociolinguistic tools of Fritz Schütze’s biographical approach and its process structures, Erving Goffman’s theory of stigma, and Anselm Strauss’s concept of social worlds, I attempt to reconstruct the processes related to influencer activity on social media. The analysis reveals tensions between the ideological vision of one’s duties and the necessity to meet the expectations of the audience, including in the context of accusations related to the commodification of queerness. The text attempts to capture the possible biographical meanings of being an influencer and the identity-related entanglements of this role. It also highlights potential disruptions to biographical work caused by activities within social media.